Evaluasi Fungsional Sistem Informasi Manajemen Kemasjidan Berbasis Web Menggunakan Metode Black Box Testing - Nur Latifah; Muhammad Taufiq; Sulidar Fitri (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2026)
Mosque management requires an integrated information system to support the management of mosque data, preachers, religious lecture schedules, and administrative activities more effectively. However, the existing management process is still largely conducted manually, resulting in data inconsistencies, scheduling conflicts, and delays in information dissemination. This study aims to evaluate the functional performance of the Web-Based Mosque Management Information System (SIMAKMU) using the Black Box Testing method. The research employed a descriptive quantitative approach by testing the main functional features of the system, including user authentication, dashboards based on user roles, mosque data management, preacher data management, lecture schedule submission, schedule confirmation, notifications, and logout functions. The testing process was carried out by comparing the expected outputs with the actual outputs generated by the system without examining the internal source code. The results indicate that all testing scenarios were successfully executed and achieved Valid status, demonstrating that every feature functioned according to the predefined system requirements. These findings indicate that SIMAKMU has fulfilled the required functional aspects and is suitable for supporting integrated mosque management activities. The implementation of the system is expected to improve administrative efficiency, facilitate coordination among mosque administrators and preachers, and minimize scheduling conflicts in Muhammadiyah mosque activities.